Four component synthesis of highly functionalized pyrano[2, 3-c]pyrazoles from benzyl halides. Issue 2 (17th January 2018) - Beerappa, Mallappa; Shivashankar, Kalegowda
ABSTRACT: N -methylmorpholine N -oxide and silver oxide (Ag2 O) oxidized four component reaction for the preparation of pyranopyrazole with different substituted pattern have been developed which provides rapid access to a library of compounds in good to excellent yields by using benzyl halide, malanonitrile/ethyl cyanoacetate, diethylacetylenedicarboxylate/ethyl acetoacetate and hydrazine hydrate as reactants. This transformation involves the breaking of one C‒O bond and formation of 2 C–C, 2 C–N, and a C‒O bond leading to the formation of a five and six membered ring in one pot operation. GRAPHICAL ABSTRACT: